(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The article examines theoretical foundations of land reform in Ukraine. The legislation on land, rights protection of land owners, foreign experience of reforming land resources of states are analyzed. It is determined that the most important reason for the imbalance of our country’s economy is the imperfection of unilateral land reform, resulting in large number of agricultural enterprises of various forms of ownership and management, which use agricultural land mainly for maximum self-enrichment, while neglecting technological norms of agricultural production as well as norms of rational land use. It is determined that foreign investors, companies with the necessary knowledge and equipment, are unsure to invest in Ukraine due to imperfect legal guarantees. The favorable legal climate is needed for improvement of agricultural sector. The land issue is largely political. The experience of foreign countries, which offer the number of alternative methods, is valid, in particular, by establishing the permit procedure for the alienation of land, the preemptive right to purchase, tax levers, and so on. It is determined that results of land reform are assessed by identifying the social, economic and environmental consequences, which are considered in physical and qualitative terms. The consequences of land reform are manifested in real economy and have the long-term impact not only on it but also on life of society. Its complex nature and acute social significance require special attention to the place of urban and rural self-government, state bodies in regulating the land market and land relations in the country. Today, results of land reform are mostly assessed in terms of quantitative characteristics with qualitative changes either not considered or determined superficially.